Reconstructing volatility: Pricing of index options under rough volatility - Peter K. Friz; Thomas Wagenhofer (Mathematical Finance, 2023)
Avellaneda et~al. (2002, 2003) pioneered the pricing and hedging of index options – products highly sensitive to implied volatility and correlation assumptions – with large deviations methods, assuming local volatility dynamics for all components of the index. We present an extension applicable to non-Markovian dynamics and in particular the case of rough volatility~dynamics.
Keywords: 519